Development of Numidia Tours Travel Agency Online Management System for Saving Client’s Time - Daheche, Ayoub; Azizul Azhar Ramli (Applied Information Technology And Computer Science, 2021)
: Nowadays people are able to make their holiday plans through internet and developing technology; and they can purchase their holiday packages online.  However, nowadays people tend to make their lives easier and convenient. Managing holidays, travel and tourism are some of the popular issues that rose with the development of technology. Next, people might waste time in the process of reserving holiday packages and hotels or any offers, because they might go to an agency to check the offers and proceed with reservation or call the agency to get information about that which it may be a bit confusing for the client.  Therefore, an online travel agency management system is proposed which is able to generate and solve the mentioned problems. The online travel agency management system consisted of five system modules is then built which involved the user as well as the system admin. Also, the system is developed based on the prototype model as a methodology of work. The importance of this project is to provide an easier method for all the clients of NUMIDIA TOURS SDN BHD comparing to the traditional method. The system will help them to choose their preferred offers from the online offers catalogue, as well making online reservation and for the payment the client will proceed with it at the agency office. In view of time saving, less time consuming by waiting in the queue at the agency office to meet agent in order to get information.